Chronic exposure to perfluorohexane sulfonate leads to a reproduction deficit by suppressing hypothalamic kisspeptin expression in mice - Xiaorui Yin; Tingting Di; Xinyuan Cao; Zhengnan Liu; Jingyan Xie; Suyun Zhang (BMC, 2021)
Abstract Background Perfluorohexane sulfonate (PFHxS) is a six-carbon perfluoroalkyl sulfonic acid found as an environmental contaminant. This study aims to investigate the effects of PFHxS exposure on female reproduction and the underlying mechanism in mice. Methods Eight-week-old ICR mice were divided randomly into four groups administered corn oil (vehicle) and PFHxS at doses of 0.5, 5, and 50 mg/kg/day for 42 days by intragastric administration. Body weight, ovarian weight, estrous cycle, follicle counts, and serum sex hormone levels were evaluated. The expression of kisspeptin and gonadotropin releasing hormone (GnRH) in the hypothalamus was also detected. Results Compared to vehicle exposure, 5 mg/kg/day PFHxS treatment prolonged the estrous cycle, especially the duration of diestrus, after 42 days of treatment. The numbers of secondary follicles, antral follicles and corpus lutea were significantly reduced in the PFHxS-treated mice. Moreover, compared with the control mice, the PFHxS-treated mice showed decreases in the serum levels of follicle-stimulating hormone (FSH), luteinizing hormone (LH), and estrogen (E2), and reduced GnRH mRNA levels, along with the lack of an LH surge. Furthermore, the PFHxS-treated mice had lower levels of kisspeptin immunoreactivity and kiss-1 mRNA in the arcuate nucleus (ARC) and anteroventral periventricular nucleus (AVPV) than the control mice. After intraventricular administration of kisspeptin-10, the numbers of secondary follicles, antral follicles and corpus lutea recovered, along with the levels of GnRH mRNA, FSH, and LH in the mice treated with 5 mg/kg/day PFHxS. Conclusion These results indicate that chronic exposure of mice to 5 mg/kg/day PFHxS affects reproductive functions by inhibiting kisspeptin expression in the ARC and AVPV regions, leading to deficits in follicular development and ovulation.